Give Me Your Tired, Your Poor? Support for Social Citizenship Rights in the United States and Europe. (February 2018) - Oser, Jennifer; Hooghe, Marc
This article investigates whether the commitment to social rights as integral to a well-functioning democracy exists among Americans in comparison with their European counterparts. In our comparison of data from the European Social Survey in 2012 with a special parallel module of the U.S. Cooperative Congressional Election Survey in 2014, the findings suggest that similar conceptions of ideal democracy are found on both sides of the Atlantic. Although Americans are less likely than Europeans to consider fighting poverty and reducing income inequality as important democratic ideals, the analysis shows that the United States is not exceptional in the existence of a social rights conception of democracy. A distinct feature of U.S. public opinion is that support for social rights is more strongly associated with a left-right divide than in Europe. The observed congruence between policy and public opinion in the United States highlights the importance of investigating the direction of causality between both phenomena.